2013
DOI: 10.1002/macp.201300203
|View full text |Cite
|
Sign up to set email alerts
|

Counterintuitive Photomodulation of the Thermal Phase Transition of Poly(methoxy diethylene glycol acrylate) in Aqueous Solution by trans–cis Isomerization of Copolymerized Azobenzenes

Abstract: The non-ionic monomer (methoxy diethylene glycol) acrylate is copolymerized with its azodye-functionalized acrylate analogue using reversible addition-fragmentation chain transfer (RAFT) polymerization. Copolymerization is increasingly diffi cult with increasing amounts of the azo-dye-bearing monomer. The resulting water-soluble polymers are thermosensitive, exhibiting lower critical solution temperature (LCST) behavior, which can be modulated by the photoinduced trans-cis isomerization of the dye. While alrea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 67 publications
0
14
0
Order By: Relevance
“…Surprisingly, both temperatures are even lower than those without UV radiation. In general, the expectation is that the increased hydrophilicity of AAAB will shift the TT toward higher values after the trans–cis isomerization. However, the observed unexpected reduction of the TT after UV radiation has been reported before only for light-responsive, amphiphilic poly­(NIPAM) derivatives . Following this idea, it can be related to the different self-assembly behavior based on the AAAB molar fraction in P­(MEO 3 MA- co -EGMA- co -AAAB).…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Surprisingly, both temperatures are even lower than those without UV radiation. In general, the expectation is that the increased hydrophilicity of AAAB will shift the TT toward higher values after the trans–cis isomerization. However, the observed unexpected reduction of the TT after UV radiation has been reported before only for light-responsive, amphiphilic poly­(NIPAM) derivatives . Following this idea, it can be related to the different self-assembly behavior based on the AAAB molar fraction in P­(MEO 3 MA- co -EGMA- co -AAAB).…”
Section: Resultsmentioning
confidence: 90%
“…Thus, its polarity as well as hydrophilicity increases. When UV radiation is off, azobenzene immediately turns back to the trans and hydrophobic state . On the basis of this unique and reversible property, the hydrophobicity of thermoresponsive polymers can be further tuned by adding azobenzene units.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22][23][24][25][26][27] Due to their hydrophobicity, the azobenzene moieties are generally incorporated into polymeric hydrogelators. [28][29][30][31][32][33] Thus, LMWGs derived from azobenzene based hydrogels are still rare. [34][35][36][37] For example, Huang et al 34 designed and synthesized an azo-dipeptide hydrogelator whose pH and salt effect behavior and gel formation ability were investigated in detail.…”
Section: Introductionmentioning
confidence: 99%
“…The effect of aggregation on LCST in azobenzene-containing statistical copolymers was described by Laschewsky et al and observed in other works. 58,59,61…”
Section: Polymer Chemistry Papermentioning
confidence: 99%